Introducing genetic testing for cardiovascular disease in primary care: a qualitative study - Middlemass, J.B.; Yazdani, M.F.; Kai, Joe; Standen, Penny; Qureshi, Nadeem (Royal College of General Practitioners, 2014)
Background: While primary care systematically offers conventional cardiovascular risk assessment, genetic tests for coronary heart disease (CHD) are increasingly commercially available to patients. It is unclear how individuals may respond to these new sources of risk information.